1996
DOI: 10.1016/0168-1702(95)01274-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics and protein profiles of prototype and wild-type rat coronavirus isolates grown in a cloned subline of mouse fibroblasts (L2p.176 cells)

Abstract: Rat coronaviruses (RCVs) infect laboratory rats and confound biomedical research results. In vitro systems developed so far have limited the growth in knowledge about RCVs by not permitting generation of plaque-cloned virus stocks, reliable isolation of RCVs from rat tissues, or growth of high titered stocks of all isolates. Due to the fact that less than 20% of L2(Percy) cells were becoming infected, sublines were produced and selected for maximal growth of RCVs. Screening of 238 cell sublines yielded L2p.176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As currently known, SDAV in vitro propagation is possible in established cell lines, such as murine fibroblasts L-2(Percy) cells, subclone L2P-41.a, LBC cells, RCV-9, and in primary rat kidney cell cultures (RKCC). In other frequently used cell lines (VERO, Hep-2, NTCT 1469, BHK-21), infection is not possible [ 15 , 28 , 70 , 101 , 102 , 103 , 104 ]. For purification and plaque assay, L-2cells, L2P-41.a, and LBC are often used [ 100 , 101 ].…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As currently known, SDAV in vitro propagation is possible in established cell lines, such as murine fibroblasts L-2(Percy) cells, subclone L2P-41.a, LBC cells, RCV-9, and in primary rat kidney cell cultures (RKCC). In other frequently used cell lines (VERO, Hep-2, NTCT 1469, BHK-21), infection is not possible [ 15 , 28 , 70 , 101 , 102 , 103 , 104 ]. For purification and plaque assay, L-2cells, L2P-41.a, and LBC are often used [ 100 , 101 ].…”
Section: Characteristicsmentioning
confidence: 99%
“…In other frequently used cell lines (VERO, Hep-2, NTCT 1469, BHK-21), infection is not possible [ 15 , 28 , 70 , 101 , 102 , 103 , 104 ]. For purification and plaque assay, L-2cells, L2P-41.a, and LBC are often used [ 100 , 101 ]. The virus samples can be stored at −60 °C for 7 years, but according to research by Jacoby et al (1975), they can become less infectious when stored at −20 °C [ 11 , 105 ].…”
Section: Characteristicsmentioning
confidence: 99%
“…RCV replicates in vitro in primary rat kidney cells, forming multinucleate syncytia typical of coronaviral infection (Bhatt et al, 1972). Virus can be detected antigenically in infected cells within 12 h and cytopathic effects can develop within 24 h. Mouse L2 fibroblasts and sublines, as well as rat LBC cells and intestinal RCV-9 cells, can also be infected (Gaertner et al, 1996a;Hirano et al, 1986;Ohsawa et al, 1996;Percy et al, 1989Percy et al, , 1990b, and L2 sublines and LBC cells can also be used for plaque assays and plaque purification (Gaertner et al, 1993b).…”
Section: B Coronaviridaementioning
confidence: 99%
“…RCV spreads primarily by direct contact with infected rats or by aerosol, and RCV remains infectious for at least 2 days when dried on plastic surfaces (Gaertner et al, 1996a). Experimental studies have demonstrated the ease of horizontal transmission of RCV (La Regina et al, 1992), but there is no evidence for intrauterine transmission.…”
Section: Epidemiologymentioning
confidence: 99%